Impact of pancreaticoduodenal arcade dilation on postoperative outcomes after pancreaticoduodenectomy. Issue 1 (January 2018) - Nakayama, Yusuke; Sugimoto, Motokazu; Kobayashi, Tatsushi; Gotohda, Naoto; Takahashi, Shinichiro; Kusumoto, Masahiko; Konishi, Masaru
Abstract: Background: The aim of this study was to investigate the impact of pancreaticoduodenal arcade (PDA) dilation on postoperative outcomes after pancreaticoduodenectomy. Methods: Consecutive patients submitted to pancreaticoduodenectomy between 2008 and 2016 underwent preoperative multi-detector computed tomography, the images of which were re-reviewed. The patients were categorized according to the grade of PDA dilation into 3 groups (remarkably-dilated, slightly-dilated, and non-dilated). Results: Among the 443 patients, 25 patients (5.6%) were categorized as remarkably-dilated PDA and 24 patients (5.4%) as having slightly-dilated PDA. The patients with remarkably-dilated PDA had undergone pancreaticoduodenectomy with additional surgical maneuvers to restore celiac arterial flow as needed, and had an uneventful postoperative recovery relative to those with non-dilated PDA. In contrast, patients with slightly-dilated PDA underwent only pancreaticoduodenectomy without additional surgical maneuvers, and developed clinically relevant postoperative pancreatic fistula (POPF) more frequently than those with non-dilated PDA (42% vs. 21%, P  = 0.021). Moreover, slightly-dilated PDA was shown to be an independent risk factor for clinically relevant POPF (odds ratio = 2.719, P  = 0.042). Discussion: For patients with PDA dilation requiring pancreaticoduodenectomy, a preoperative evaluation of the vascular anatomy, intraoperative assessment of the celiac arterial flow, and additional surgical maneuvers might be necessary to reduce the risk of postoperative complications.